Strategic Efforts of the Yogyakarta Special Region Police Preventing Disciplinary Violations Among Police Officers in the Contexst of Law Enforcement - Masri Adam (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
This study aims to analyze the strategies implemented of the Yogyakarta Regional Police in preventing disciplinary violations, particularly in the context of law enforcement duties. Disciplinary violations committed by police officers not only cause internal harm to the institution but also negatively impact the public image of the police and diminish public trust in the law enforcement system. This research employs a descriptive qualitative approach using a normative-empirical method. The findings indicate that the Yogyakarta Regional Police have implemented several preventive strategies, including mental and religious development programs, enhancement of internal supervision, personnel rotation, and the strict enforcement of disciplinary sanctions. Although these strategies have contributed to a decline in the number of violations in recent years, their implementation still faces several challenges, such as limited human resources, suboptimal hierarchical supervision, and inconsistent enforcement of sanctions. This study recommends strengthening technology-based supervision systems, enhancing the capacity of supervisory personnel, and encouraging active leadership involvement in fostering a sustainable culture of discipline and professionalism.